Komunikasi Pemasaran Pengelolaan Air Terjun Sikulikap dalam Menarik Pengunjung Wisatawan di Kecamatan Berastagi - Fauzi, Muhammad; Riadi, Selamat (Mahesa Research Center, 2025)
The development of business in the field of tourism objects is currently very rapid, giving rise to competition to attract tourists. Rapid changes in the business environment have forced tourist attractions to continue to be active and creative in developing existing tourist sites and continuously making updates regarding strategies in marketing them. This study aims to determine